2015
DOI: 10.1186/s13071-015-1103-z
|View full text |Cite
|
Sign up to set email alerts
|

T. gondii rhoptry protein ROP18 induces apoptosis of neural cells via endoplasmic reticulum stress pathway

Abstract: BackgroundThe neurotropic parasite T. gondii is widespread among mammalian hosts including humans. During the course of T. gondii infection, the central nervous system is the most commonly damaged of all invasive organs. The polymorphic rhoptry protein ROP18 has been identified as a key factor in the pathogenesis of T. gondii; however, the molecular mechanism by which this protein exerts neuropathogenesis remains elusive.MethodsImmunofluorescence staining was performed to detect neuropathogenesis of the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 40 publications
2
39
0
2
Order By: Relevance
“…Apoptosis is also induced during T. gondii infection. TgGRA15, TgROP16, and TgROP18 were involved in triggering neuroblastomal and choriocarcinoma apoptosis (An et al, ; Chang et al, ; Wan et al, ; Wei et al, ). Induction of apoptosis in immune cells (lymphocytes, natural killers, and macrophages) contributes to evasion of the host's immune defence during the acute phase of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is also induced during T. gondii infection. TgGRA15, TgROP16, and TgROP18 were involved in triggering neuroblastomal and choriocarcinoma apoptosis (An et al, ; Chang et al, ; Wan et al, ; Wei et al, ). Induction of apoptosis in immune cells (lymphocytes, natural killers, and macrophages) contributes to evasion of the host's immune defence during the acute phase of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled tachyzoite replication may cause severe and potentially life-threatening encephalitis. It is well known that encephalitis caused by T. gondii can be lethal, due to tissue inflammation, apoptosis, and/or necrosis, as well as other complex pathological processes (2,8,10,11,21). However, the mechanism of TE is still unclear despite a variety of hypotheses that have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies revealed that ROP18 phosphorylates the host NF-κB p65 and targets this protein to ubiquitin-dependent degradation, thus inhibiting the NF-κB pathway in infected macrophages (17). In addition, our recent studies have demonstrated that ROP18 can stimulate neural cell death by inducing the ER stress-mediated apoptosis pathway (10). However, host proteins, especially those preferentially expressed in nervous tissues, targeted by ROP18 and its associated molecular mechanism remain unclear.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The dopamine content in cortical and hippocampus areas of the male offspring rats infected with T. gonodii is higher than that non‐infected control (Zhou et al, ). Moreover, T. gondii tachyzoites induces neural apoptosis in hippocampus and cortical areas of the infected mice, which might be responsible for neurological disorders of toxoplasmosis (Wan et al, ). It is also reported, 30 days after T. gondii infection, mice display spontaneous electrographically recorded seizures.…”
Section: Discussionmentioning
confidence: 99%